2 + 2 = 5: A ideologia em Nineteen Eighty-Four de George Orwell - Bispo, Jessica (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
Taking into account the society represented in the novel Nineteen Eighty-Four (1949), by George Orwell, this article offers an analysis of the methods used by its ruling government to secure the consolidation and spreading of its ideology, by establishing a comparison with philosopher Louis Althusser‘s theory concerning the structures of the State and its Ideological Apparatuses, which allow to maintain and spread certain ideals. Thus, it will be possible to understand the organization of the Party holding all the power in Orwell‘s imagined society and how it ensures the population‘s quiescent submission. Despite the extreme control exerted in this dystopian society, our analysis also seeks to expose the existence of dissenters, exploring how they subvert the Party‘s ideology and the resources it uses to smother transgressions to the imposed standards.